PENGARUH KONTEN EDUKATIF MELALUI APLIKASI TIKTOK DAN MOTIVASI BELAJAR INFORMATIKA TERHADAP POLA PIKIR JREATIF SISWA KELAS VIII MTSN 7 BUNGO - Saputri, Wanda (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
This research wants to find out how Educational Content and Learning Motivation affect the Creative Thinking Patterns of eighth graders at MTsN 7 Bungo. The study used number-based methods, specifically simple linear regression and multiple linear regression analysis. To collect data, they used a survey and checked to make sure it was valid and reliable. Before doing regression analysis, the data was examined for reliability using a test called Cronbach's Alpha, which was greater than 0.6, showing the survey was reliable. After that, they checked for normal distribution with a Kolmogorov-Smirnov test, which showed normal distribution (Sig. > 0.05), and they also did a linearity test that confirmed a linear relationship between the factors (Sig. > 0.05). The partial hypothesis test, known as the t-test, showed that both Educational Content and Learning Motivation had a positive and significant influence on Creative Thinking Patterns when looked at separately. However, in the multiple regression analysis, only Learning Motivation had a significant impact, while Educational Content did not, even though it still had a positive influence. An R-squared value of 0.400 means that Educational Content and Learning Motivation account for 40% of the changes in Creative Thinking Patterns, while the other 60% is affected by other factors not examined in this study. Therefore, we can say that Learning Motivation is the main factor affecting how students think creatively, while Educational Content supports that in a smaller way.